Modified blue TiO2 nanostructures for efficient photo-oxidative removal of harmful NOx gases - Nguyen, Hao Huy; Gyawali, Gobinda; Martinez-Oviedo, Adriana; Nguyen, Hoang Phuc; Lee, Soo Wohn (The Korean journal of chemical engineering, 2020)
Blue TiO 2 nanostructures were produced via Lithium/ethylenediamine (Li/EDA) reduction method and applied for photo-oxidative removal of harmful NO x gases under simulated solar light irradiation. Blue TiO 2 possesses some unique physicochemical properties such as enhanced visible-light absorption, superficial defects or oxygen vacancies, and the evolution of Ti 3+ species. Moreover, the photoluminescence spectra (PL) revealed the efficient separation of photoinduced electron-hole pairs in the modified blue TiO 2 nanostructures, enhancing their photocatalytic activities. The results indicated that the blue TiO 2 nanostructures exhibited the highest performance towards photo-oxidation of NO x gases, with an efficiency of 72.6% under simulated solar light irradiation.